Study of two-layered circular patch using moment method and genetic algorithms - Ahmed Mahamdi; Siham Benkouda; Mounir Amir; Sami Bedra (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, new expressions for the effective radius and fringing capacitance have been derived to predict accurately the resonant frequency of the two-layered circular microstrip patch antenna. These expressions are obtained based on genetic algorithm and the data base is generated using moment method (MOM). The proposed model is very simple, fast, and valid for an entire range of permittivities and thicknesses of two-layered substrate. The present model has been validated by comparing our numerical results obtained for the resonant frequencies with measurements. Finaly, the effect of the two-layered substrate on the resonant charateristics of the circular microstrip patch antenna has been presented.